2021
DOI: 10.13057/biodiv/d220854
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of non-symbiotic nitrogen-fixing bacteria and their potential in andisols affected by the eruption of Mount Sinabung, North Sumatra, Indonesia

Abstract: Abstract. Sembiribg M, Sabrina T. 2021. Diversity of non-symbiotic nitrogen-fixing bacteria and their potential in andisols affected by the eruption of Mount Sinabung, North Sumatra, Indonesia. Biodiversitas 22: 3539-3544. Nitrogen is the main macro-nutrient that is very important for plant growth. Nitrogen is absorbed by plants in the form of NO3-or NH4+ ions from the soil. The andisols affected by the eruption of Mount Sinabung alter the chemical, physical and biological characteristics of the soil. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…With the mixed inoculant, the role of each bacteria can function properly so that plant growth increases compared to a single treatment. Nitrogen-fixing bacteria can produce IAA hormone so that it can increase plant growth 2,[19][20][21][22] . According to Paul et al 23 , E. cloacae can increase nitrogen-fixation so that it increases plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…With the mixed inoculant, the role of each bacteria can function properly so that plant growth increases compared to a single treatment. Nitrogen-fixing bacteria can produce IAA hormone so that it can increase plant growth 2,[19][20][21][22] . According to Paul et al 23 , E. cloacae can increase nitrogen-fixation so that it increases plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the fertilizer treatment which combined 3 types of fertilizers namely urea, LOF, and NFB (P6) gave the highest total N content, namely 0.95% (very high category [19]) and was significantly different from other treatments. This is presumably because the A4 treatment is a complete fertilizer combination from this study, namely urea with a high enough N content can increase total N [22], LOF based on initial analysis contains very high total N, and NFB plays a role in nitrogen fixation in the air [20].…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 92%
“…The presence of nitrogen-fixing bacteria plays a role in fixing nitrogen in the air so that it can increase the total N in the soil. Research [20] reported that N-total increased by 111.76 % in soil applied with NFB compared to without NFB application. In addition, biochar can absorb NH 4 + and NO 3thereby reducing the leaching and evaporation of N from the soil [21].…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 99%
“…Nitrogen-fixing bacteria can be found in soil and plant roots [13,14]. Nitrogen-fixing bacteria consist of non-symbiotic bacteria that fix free nitrogen in the air without associating with other organisms and symbiotic bacteria that fix nitrogen by associating with other organisms.…”
Section: Introductionmentioning
confidence: 99%